An examination of constraint-induced therapy as a method to intensify intervention and improve functional outcome during the rehabilitation phase of stroke - Ploughman, Michelle, 1966- (2003)
Thesis (M.Sc.)--Memorial University of Newfoundland, 2003. Medicine Bibliography: l. 118-122.